Modern views in the Pathogenesis of Stroke (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Our report analyzes data from a study on the parameters of the intensity of free radical processes and indicators of the state of the antioxidant defense system of enzymatic and non-enzymatic components in patients with stroke in the aspect of verifying oxidative stress in the pathogenesis of this disease.